SNAP and/or WIC Participation and Diet Quality in Mother-Child Dyads living in Greater Boston after Pandemic: A Mixed-Method Study - Thanit Vinitchagoon; Fang Fang Zhang; Rebecca C. Fauth; Erin Hennessy; Ana G. Maafs; Emma M. Browning; Christina D. Economos (Journal of Primary Care & Community Health)
Introduction/Objectives: Since the COVID-19 pandemic, few studies have examined how participation in Supplemental Nutrition Assistance Program (SNAP) and/or Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) impacts diet quality in families with young children. This study aims to explore the association between SNAP and/or WIC participation and diet quality in mother-child dyads in Greater Boston, MA. Methods: A mixed-method approach involving cross-sectional surveys and in-depth interviews were utilized. Participants included 69 mother-child dyads for quantitative and 18 mothers for qualitative data collection. Analysis of covariance using generalized linear models was employed to compare differences in Healthy Eating Index-2015 (HEI-2015) scores based on SNAP and/or WIC participation, and thematic analysis was used for coding themes. Results: Mothers who participated in SNAP and/or WIC were more from lower socioeconomic backgrounds. After adjusting for age, race/ethnicity, and education, no significant differences in diet quality were found for both mothers and their children. However, qualitative results showed that mothers prioritized their children’s nutrition, used benefits to buy fruits and vegetables, and experienced stress that impacted their own diet quality. Conclusions: Since the pandemic, SNAP and WIC appeared to support families experiencing socioeconomic disadvantage (e.g., lower income and educational attainment) to improve diet quality, particularly through increased access to fruits and vegetables. However, these programs have not fully eliminated persistent disparities in diet quality, which seems to continue even the pandemic’s immediate effects have subsided.